(In)visibles persévérances de l’absence. Les enjeux de la mise en forme dans Les Années d’Annie Ernaux - Rachwalska von Rejchwald, Jolanta (Quêtes littéraires, 2011)
A dialectic between presence and absence, remembrance and oblivion, testimony and silence, body and its trace reflects the gist of the most recent Ernaux’es book. It constitutes not only plenteaus thematic confluence but also or even majorly an axis of the book’s construction. Its structure encompasses various layers such as: rhetorical, stylistic and typographic, which separately and together combined reside in prevailing tensioned coexistence of presence and absence.